2009
DOI: 10.1186/1477-7827-7-108
|View full text |Cite
|
Sign up to set email alerts
|

Miscarriage rates after dehydroepiandrosterone (DHEA) supplementation in women with diminished ovarian reserve: a case control study

Abstract: Background: Dehydroepinadrosterone (DHEA) supplementation improves pregnancy chances in women with diminished ovarian reserve (DOR), by possibly reducing aneuploidy. Since a large majority of spontaneous miscarriages are associated with aneuploidy, one can speculate that DHEA supplementation may also reduce miscarriage rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 27 publications
4
73
0
1
Order By: Relevance
“…In addition to these encouraging studies, no significant differences in clinical pregnancy rates and miscarriage rates between DOR women pre-treated with DHEA, compared to those without DHEA pre-treatment were found in a recent meta-analysis [Narkwichean et al 2013]. Because the probable effect of DHEA on patients with DOR is still not clear, the proposed mechanisms obtained from clinical studies, such as improved follicular steroidogenesis, increased IGF-1 [Casson et al 2000] acting as a pre-hormone for follicular testosterone [Gelicher and , reducing aneuploidy Gleicher et al 2009], and increasing AMH with antral follicle count [Andersen and Lossi 2008] remain speculative. Narkwichean et al [2014] conducted studies using an experimental sheep model to search for the effects of exposure of ovarian tissue to DHEA supplementation in vivo, and this study was the first to evaluate the effect of DHEA treatment on early follicle development in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these encouraging studies, no significant differences in clinical pregnancy rates and miscarriage rates between DOR women pre-treated with DHEA, compared to those without DHEA pre-treatment were found in a recent meta-analysis [Narkwichean et al 2013]. Because the probable effect of DHEA on patients with DOR is still not clear, the proposed mechanisms obtained from clinical studies, such as improved follicular steroidogenesis, increased IGF-1 [Casson et al 2000] acting as a pre-hormone for follicular testosterone [Gelicher and , reducing aneuploidy Gleicher et al 2009], and increasing AMH with antral follicle count [Andersen and Lossi 2008] remain speculative. Narkwichean et al [2014] conducted studies using an experimental sheep model to search for the effects of exposure of ovarian tissue to DHEA supplementation in vivo, and this study was the first to evaluate the effect of DHEA treatment on early follicle development in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that DHEA improved the outcomes of IVF by reducing aneuploidy and improving ovarian reserve (25,61). The current study found that administration of DHEA tended to delay the loss of cohesin in oocytes and thus reduce the rate of oocyte aneuploidy.…”
Section: Discussionmentioning
confidence: 49%
“…Also, DHEA resulted in a similar improvement in patients with age-dependent diminished ovarian reserve and patients with premature ovarian insufficiency. Similar outcomes were suggested by another group [22], who studied forty seven patients with prior clomiphene citrate failures and were supplemented with 75 mg of DHEA daily for at least 60 days prior to stimulation with either letrozole or clomiphene citrate in combination with FSH [22]. Another study evaluated the outcome of nineteen poor responder patients undergoing IVF supplemented with DHEA for at least 3 months.…”
Section: Published Studiesmentioning
confidence: 58%
“…The apparent improvement in miscarriage rate and IVF pregnancy rate may be explained by improving embryo ploidy [22,23]. The risk of age related aneuploidy is explained by major disturbances in chromosomes alignments on the meiotic spindle of oocytes which is primarily caused from the complex interplay of inter and intracellular signals regulating follicular development.…”
Section: Mechanism(s) Of Actionmentioning
confidence: 99%